Afghanistan Development Update, June 2019 : Building Confidence Amid Uncertainty - World Bank (World Bank, Washington, DC, 2019)
Afghanistan faced severe economic headwinds in 2018, with the economy growing by an estimated 1.8 percent. Slow growth was driven by two major factors. Firstly, severe drought had a strong negative impact on agricultural production. Agricultural growth slowed to 0.8 percent as low snowfall during late 2017 and early 2018 led to the loss of grain crops and livestock productivity. Secondly, business and investor confidence deteriorated significantly in the context of elevated uncertainty around: i) the level and duration of international security assistance; ii) the outcome of upcoming presidential elections (now delayed until September); iii) prospects of continued or worsening election-related violence (civilian deaths reached their highest level since 2001); and iv) ongoing peace negotiations with the Taliban. Real GDP growth is expected to have accelerated during the first half of 2019, mainly driven by the easing of drought conditions and improved agricultural production. Intensifying political uncertainties, however, are expected to have continued to dampen private sector confidence and investment. Poverty is estimated to have increased and deepened. The rate of economic growth substantially lagged population growth, leading to declining per capita incomes. The drought negatively impacted livelihoods of many of the 82 percent of the poor living in rural areas, including those reliant on poppy cultivation (poppy production declined by 30 percent). Reflecting widespread hardship, drought-induced displacement reached record levels of 298,582 individuals, mainly to urban areas in adjacent provinces.